Case report: HLA-haploidentical hematopoietic cell transplant with posttransplant cyclophosphamide in a patient with leukocyte adhesion deficiency type I - Yamashita, Motoi; Eguchi, Shiori; Tomomasa, Dan; Kamiya, Takahiro; Niizato, Daiki; Mitsuiki, Noriko; Isoda, Takeshi; Funakoshi, Hanako; Mizuno, Yuki; Okamoto, Kentaro; Nguyen, Tuan Minh; Takada, Hidetoshi; et al. (Frontiers in Immunology, 2022)
Leukocyte adhesion deficiency type I (LAD-I) is a rare autosomal recessive inborn error of immunity (IEI) caused by the defects in CD18, encoded by the ITGB2 gene. LAD-I is characterized by defective leukocyte adhesion to the vascular endothelium and impaired migration of leukocytes. Allogeneic hematopoietic cell transplant (HCT) is the only curative treatment for LAD-I. In an absence of ideal donor for HCT, human leukocyte antigen (HLA)-haploidentical HCT is performed. Posttransplant cyclophosphamide (PT-CY) is a relatively new graft-versus-host disease (GVHD) prophylactic measure and has been increasingly used in HLA-haploidentical HCT for malignant and nonmalignant diseases. However, experience in using PT-CY for rare IEIs, such as LAD-I, is very limited. We report a case of LAD-I successfully treated with HLA-haploidentical HCT with PT-CY. Complete chimerism was achieved, and the patient was cured. Her transplant course was complicated by mild GVHD, cytomegalovirus reactivation and veno-occlusive disease/sinusoidal obstruction syndrome, which were successfully treated. HLA-haploidentical HCT with PT-CY is a safe and effective option for patients with LAD-I when HLA-matched donors are unavailable.